Cyberbullying Relationship with Social Anxiety and Social Withdrawal in Adolescents - Fahlevi, Restu Yogi; Yusuf, Ah; Krisnana, Ilya (Fundamental and Management Nursing Journal, 2020)
Introduction: The process of changing a person into adolescence is a very important process where in adolescence, the process of finding the identity of a teenager is ongoing, looking for self-identity, trying new things, and social processes such as having a group of friends who he thinks have one hobby with him. Commonly referred to as "gangs", the characteristics of adolescents who are in the process of seeking their own identity often cause negative problems in their environment, including cyberbullying.Methods: The study design was cross sectional. A sample of 262 students of class xi and obtained using simple random sampling technique. Data obtained from the Cyberbullying and Online Aggression Survey Instrument questionnaire and The Social and Emotional Competences Evaluation Questionnaire (QACSE) were then analyzed using the Spearman Rho correlation statistical test.Results: The results of this study indicate that there is a relationship between Cyberbullying and social anxiety in adolescents. It was found that the higher the Cyberbullying obtained, the higher the social anxiety experienced by adolescents with a value of p = 0.000; r = 0.225 normal value p = 0.05, r = 1. There is a relationship between cyberbullying and social withdrawal in adolescents with a value of p = 0.009; r = 0.161 with a normal value of p = 0.05 and r = 1.Conclusion: Cyberbullying on social anxiety has a low and significant relationship with a negative direction where the higher the involvement of adolescents with cyberbullying is lower and Cyberbullying on social withdrawal has a low and significant relationship in a negative direction where the higher the adolescent involvement with cyberbullying is lower.